Effect of positional release technique along with high velocity low amplitude thrust in sacroiliac joint dysfunction - s. Nikam, Gauri; Rayjade, Amrutkuvar; mohite, shraddha; khilwani, Amruta (International Journal of Psychosocial Rehabilitation, 2020)
Objective: The purpose of this topic was to study the effect of positional release technique along with high-velocity, low-amplitude thrust in sacroiliac joint dysfunction.Method: 50 subjects diagnosed with sacroiliac joint dysfunction were included in this study. The age group 21-50 was added in the study. These subjects were allocated by lottery method into 2 groups (group A—hot moist pack, positional release technique, and exercises; and group B—hot moist pack, positional release technique, high-velocity low-amplitude thrust, and exercises). Before and after the treatment protocol, the subjects were assessed for pain by the Short Form of the McGill Questionnaire and the Modified Oswestry Low Back Pain Questionnaire used for functional mobility. These outcome measures were analyzed.Result: Pre- and post-treatment protocols were analyzed by using paired and unpaired t-tests. Data analysis showed extreme significance for both the Short Form of the McGill Questionnaire (p=0.0001) and the Modified Oswestry Low Back Pain Questionnaire (p=0.0001).